Hemophagocytic Lymphohistiocytosis Complicated by Acute Respiratory Distress Syndrome and Multiorgan Failure. (November 2021) - Liu, Louisa; Bashir, Hanad; Awada, Hassan; Alzubi, Jafar; Lane, Jason
Hemophagocytic lymphohistiocytosis (HLH) is a rare and life-threatening condition that is characterized by an overactive response of the immune system with excessive production of proinflammatory cytokines. Initial presentation of this condition often mimics and overlaps with many diseases including infections, sepsis, and multiorgan failure syndrome, which makes diagnosis the diagnosis of HLH challenging. Herein is described a case of a patient who developed acute respiratory distress syndrome and multiple organ failure related to HLH in a setting of probable viral pneumonia. The diagnosis was established based on laboratory and bone marrow biopsy findings. This patient was treated with the standard chemotherapy regimen of intravenous dexamethasone, etoposide in addition to intrathecal methotrexate for central nervous system involvement.